Proposta de um transmissor de dados portátil e de baixo custo para o processo eleitoral Brasileiro - Lima, João Henrique de (2013)
The use of information technology to promote the automation of work processes is widely spread. Systems to automate the manufacturing processes and to support services delivery help to improve the productivity and have become an indispensable asset to be exploited by organizations wishing to have the competitive advantages essential to survive in a crowded marketplace. In the context of public sector, the automation process also moves quickly and new tools that streamline and reduce the costs of providing services to citizens are being implemented. The Brazilian electoral process followed the wave of informatization and is fully automated since 1998. However, the informatization of elections is a critical process due to various requirements related to the electoral process security. The scenario of an electoral process is composed of a set of interests, often conflicting, which should be harmonized by fair and clean elections. Computerization has advantages related to greater agility in the process of calculation and disclosure of the outcome of the elections, greater economy, greater flexibility, possibility of correcting errors made at the time of voting, inclusion of people with disabilities, among others. Reconcile the difficulties of implementing the requirements in an electoral system, specifically those conflicting, which shall ensure the legitimacy of the elections (voter privacy and guarantee of the integrity), to take advantage of the benefits that computerization provides, has been subject of academic research. This work presents a project to build a prototype of an embedded device that aims to increase economicity of the Brazilian electoral process. The device is intended to improve the activity of sending files containing the electronic votes, acquired in the Brazilian electronic ballot boxes, for counting and obtaining the result of the election. To improve security, the prototype makes use of encryption techniques to ensure that the channel used for transmission of results is secure. The economy for the electoral process will be guaranteed with a portable, lightweight, low energy consumption and robust device. Portable and smaller equipments can reduce the costs with the acquisition process, preparing and sending to the places where the electronic votes will be transmitted in order to be aggregated in centralized systems.